Case studies in computer-aided molecular design (CAMD) of low- and medium-grade waste-heat recovery ORC systems - van,Kleef LMT; Oyewunmi,OA; Harraz,AA; Haslam,AJ; Markides,CN (ECOS, 2018)
Organic Rankine cycle (ORC) engines are suitable for theconversion oflow-grade heat into useful power. While numerous substances are available asORC working-fluid candidates, computer-aided molecular design (CAMD) techniques allow the rigorous selection of an optimal working fluid during system optimisation. The aim of this present study is to extend an existing CAMD-ORC framework [1,2] by incorporating, in addition to thermodynamic performance objectives, economic objectives when determining the optimal systemdesign, while maintaining the facility of selecting optimal working fluids. The SAFT-γ Mie equation of state is used to predictthethermodynamic properties of theworking fluids(here, hydrocarbons)that are relevant to the systems’economic appraisalsand critical/transport properties are estimated using empirical group-contribution methods. System investment costs are estimated with equipment cost correlations for the key system components, andthe stochastic NSGA-II solver is used for system optimisation. From a set of NLP optimisations, it is concluded that the optimal molecular size of the working fluid is linked to the heat-source temperature. The optimal specific investment cost (SIC) values were £10,120/kW and£4,040/kW when using heat-source inlet temperatures of 150°Cand250°C (representative of low-and medium-gradeheat) respectively, andthe corresponding optimal working fluids were propane, 2-butane and 2-heptene.